2006
DOI: 10.1002/ejoc.200500791
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene‐Supported 1,5,7‐Triazabicyclo[4.4.0]dec‐5‐ene as an Efficient and Reusable Catalyst for the Thiolysis of 1,2‐Epoxides under Solvent‐Free Conditions

Abstract: Polystyrene-supported 1,5,7-triazabicyclo[4.4.0]dec-5-ene (PS-TBD) is an effective basic catalyst for the thiolysis of the 1,2-epoxides 1a-e by the aryl-and alkyl-substituted thiols 2A-E under solvent-free conditions while its activity is remarkably reduced in MeCN. The reactions are totally antidiastereoselective and generally highly C-β regioselective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…In the last few years, we have been contributing in this field and we have demonstrated that solvent‐free conditions (SolFC) have beneficial effects on some organic transformations,7 such as Michael additions,7a,7j oxirane ring‐opening reactions,7e,7f Diels–Alder reactions,7g7i and [3+2]7c,7d and 1,3‐dipolar7b cycloadditions allowing the chemically and environmentally efficient preparation of target molecules such as 1 H ‐1,2,3‐triazoles, 1 H ‐tetrazoles, biphenyl‐2‐ylcarbonitriles, and benzo[ e ]1,4‐oxathiepin‐5‐ones among others.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, we have been contributing in this field and we have demonstrated that solvent‐free conditions (SolFC) have beneficial effects on some organic transformations,7 such as Michael additions,7a,7j oxirane ring‐opening reactions,7e,7f Diels–Alder reactions,7g7i and [3+2]7c,7d and 1,3‐dipolar7b cycloadditions allowing the chemically and environmentally efficient preparation of target molecules such as 1 H ‐1,2,3‐triazoles, 1 H ‐tetrazoles, biphenyl‐2‐ylcarbonitriles, and benzo[ e ]1,4‐oxathiepin‐5‐ones among others.…”
Section: Introductionmentioning
confidence: 99%
“…We have used flow technology as an effective mixing technology in the combination of heterogeneous catalysts (organic and organometallic) and green reaction media such as azeotropes, water and also solventfree conditions proving that with this approach the chemical efficiency as well as the greenness of a synthetic methodology can be effectively maximized and some examples will be described below [66,[69][70][71][72][73][74][75][76][77][78].…”
Section: Flow Technologymentioning
confidence: 99%
“…The PS-TBD catalyst has been shown to be effective for epoxide ring opening reactions with several nucleophiles such as thiols under solvent free conditions [37,78] (Scheme 6.21). In this case, the reusability of the catalyst was also established without a significant loss of reactivity and selectivity.…”
Section: Miscellaneousmentioning
confidence: 99%